Ernst Boerschmann : Das unveröffentlichte Werk „Pagoden II". - Walravens, Hartmut (Abhandlungen für die Kunde des Morgenlandes., 2016)
Ernst Boerschmann (1873-1949) was a pioneer and is still the most prominent representative of Chinese architectural research in Europe. From 1906 to 1909 he traveled to China, photographed and measured the most important buildings and published his results. His work inspired the founding of a Chinese Society for Building Research (1929). Realizing that in China, as in Europe, many of the most important buildings had religious origins, he published the three-volume work The Architecture and Religious Culture of the Chinese. The second part of the monograph on the pagodas could not be printed due to the political and economic situation, although it was completed and continuously updated until the end of the Second World War. It was later thought to be missing and it is fortunate that a carbon copy was found which served as the basis for the original publication. Boerschmann, professor at the Technical University of Berlin, not only brought solid specialist knowledge with him, but also relied on his own research on site, mastered the Chinese language and, above all, the German language - he wrote in a clear and understandable style. His work is still exemplary today, especially since there is no study that has replaced his pagoda work. In addition, many a building no longer exists today, or not in the form it was then, or it is not accessible. Many of the illustrations come from Boerschmann himself or are historical photos from other sources. Three parts in one volume: Tianning Pagodas, Lama Pagodas, Biyunsi (Temple of Azure Clouds) and historical images. Chinese writing is included and the text is indexed.